2022
DOI: 10.1002/mc.23437
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional and metabolic remodeling in clear cell renal cell carcinoma caused by ATF4 activation and the integrated stress response (ISR)

Abstract: Research has shown extensive metabolic remodeling in clear cell renal cell carcinoma (ccRCC), with increased glutathione (GSH) levels. We hypothesized that activating transcription factor‐4 (ATF4) and the integrated stress response (ISR) induce a metabolic shift, including increased GSH accumulation, and that Vitamin A deficiency (VAD), found in ccRCCs, can also activate ATF4 signaling in the kidney. To determine the role of ATF4, we used publicly available RNA sequencing (RNA‐seq) data sets from The Cancer Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 60 publications
1
9
0
Order By: Relevance
“…2 In line with these findings, another report showed increased glutathione in clear cell renal cell carcinoma associated with the ATF4-dependent activation of ALDH1L2 expression. 39 The function of ALDH1L2 in supporting the redox status of the cell was also demonstrated in our Aldh1l2 knockout (Aldh1l2 À/À ) mouse model. 5 Aldh1l2 À/À mice compared to Aldh1l2 +/+ mice had significantly decreased levels of NADPH and experienced increased oxidative stress as judged based on the overall metabotype analysis.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…2 In line with these findings, another report showed increased glutathione in clear cell renal cell carcinoma associated with the ATF4-dependent activation of ALDH1L2 expression. 39 The function of ALDH1L2 in supporting the redox status of the cell was also demonstrated in our Aldh1l2 knockout (Aldh1l2 À/À ) mouse model. 5 Aldh1l2 À/À mice compared to Aldh1l2 +/+ mice had significantly decreased levels of NADPH and experienced increased oxidative stress as judged based on the overall metabotype analysis.…”
Section: Discussionsupporting
confidence: 57%
“…In agreement with this mechanism, interference with this pathway in cultured cells resulted in decreased cellular NADPH/NADP + and reduced/oxidized glutathione ratios, and increased cell sensitivity to oxidative stress 2 . In line with these findings, another report showed increased glutathione in clear cell renal cell carcinoma associated with the ATF4‐dependent activation of ALDH1L2 expression 39 …”
Section: Discussionmentioning
confidence: 60%
“…Although we did not intensively study the mechanistic details how the metabolic reprogramming is regulated in IECs, several recent publications suggest that a PERK-ATF4-dependent activation of the integrated stress response (ISR) is important for the observed metabolic adaptation upon ER-stress (73)(74)(75). CHIPseq data already demonstrated that PHGDH, PSAT1, SHMT2, MTHFD2 and ALDH1L2 are direct ATF4 targets (76).…”
Section: Discussionmentioning
confidence: 99%
“…Although the mechanistic basis for the metabolic reprogramming in IECs deserves to be resolved in more detail, recent studies suggest a critical role for the PERK-ATF4-pathway and the integrated stress response (ISR) (72)(73)(74). CHIPseq data already demonstrated that PHGDH, PSAT1, SHMT2, MTHFD2 and ALDH1L2 are direct ATF4 targets (75).…”
Section: Discussionmentioning
confidence: 99%
“…Further studies found that the expression of TRIB3 increased with the development of clinical stage, pathological grade, and primary tumor size, indicating that TIRB3 promoted the ccRCC progression and increased the risk of invasion and deterioration of ccRCC (Wu et al, 2022). In addition, normoxic HIF1α signaling in the murine TRAnsgenic Cancer of the Kidney (TRACK) model for early‐stage ccRCC, increase TRIB3 messenger RNA levels, and increase levels of lipids and GSH (van der Mijn et al, 2022). Elevated TRIB3 expression is a prognostic marker in patients with ccRCC, suggesting that TRIB3 has a novel molecular mechanism in ccRCC.…”
Section: Discussionmentioning
confidence: 99%